THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) AND LOCAL LANGUAGES OF PAPUA IN ENGLISH LANGUAGE TEACHING (ELT) TO IMPROVE STUDENTS’ VOCABULARY - Upi Laila Hanum (Journal of English Educational Study (JEES), 2021)
This research was conducted to examine the effectiveness of the use of Information and Communication Technology (ICT) especially PicLits and Kahoot! and local languages of Papua in English Language Teaching (ELT) to improve students’ vocabulary. Method of the research was action research which consisted of two cycles. The data of the research was collected from 72 students of Informatics Engineering, University of Science and Technology, Jayapura (USTJ). The results of the research showed that the use of ICT in ELT was effective in improving students’ vocabulary, while the use of local languages of Papua was not effective. The main score of pre-test was 32. There were only 7 (10%) students who achieved passing grade in the test. The mean score of students improved to 67 in post-test and there were 57 (79%) students who passed the passing grade in the test. The data also implied that the use of ICT in the English Language Teaching (ELT) made students interested in learning, motivated, active and participative in the class.